KAJIAN PERGESERAN KERJA WANITA DARl TENAGA PEMETIK TEH KE JEN1S PEKERJAAN LAINNYA (KASUS D1 DESA SEKITAR PERKEBUNAN TEH PT. SARANA MAND1RI MUKTI KABUPATEN KEPAHIANG) - Arianti, Nyayu Neti; Priyono, Basuki Sigit (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2010)
This research is aimed to investigate: 1) which jobs were chosen by women who worked as the tea leaves pickers at P'I'Barana Mandiri Mukti Plantation in Kabupaten Kepahiang after they have fined due to the collapse of the plantation, 2) the women's working time in their new job, 3) their income from their new job and 4) their income contribution to their family income. The snowball sampling was used to take the 60 respondents. The primary data were collected through interview and the secondary data were taken from other institutions related to this research. The research results showed that there were 31J% respondents had new job as the helper of their husband working on their own farm, 20% worked to clear weeds away at other tea plantation, 16J% as the pickers at other tea plantations and 11,7% as housewives. The women worked 4,8 hours/day on an average at their new job. The average of the women's income from their new job was Rp 282.833,30/month and their contribution to their family income was 35,96 on an average and it is classified on low category.